2008
DOI: 10.1124/jpet.108.142950
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipopolysaccharide-Stimulated Chronic Obstructive Pulmonary Disease Macrophage Inflammatory Gene Expression by Dexamethasone and the p38 Mitogen-Activated Protein Kinase Inhibitor N-cyano-N′-(2-{[8-(2,6-difluorophenyl)-4-(4-fluoro-2-methylphenyl)-7-oxo-7,8-dihydropyrido[2,3-d] pyrimidin-2-yl]amino}ethyl)guanidine (SB706504)

Abstract: p38 mitogen-activated protein kinase (MAPK) signaling is known to be increased in chronic obstructive pulmonary disease (COPD) macrophages. We have studied the effects of the p38 MAPK inhibitor N-cyano- pyrimidin-2-yl]amino}ethyl)guanidine (SB706504) and dexamethasone on COPD macrophage inflammatory gene expression and protein secretion. We also studied the effects of combined SB706504 and dexamethasone treatment. Lipopolysaccharide (LPS)-stimulated monocyte derived macrophages (MDMs) and alveolar macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 36 publications
9
57
0
Order By: Relevance
“…Therefore, overcoming corticosteroid insensitivity by using p38 MAPK inhibitors can be demonstrated in severe asthmatics. Our data are supported by a recent study that reported that a p38 MAPK inhibitor in combination with dexamethasone caused a greater suppression of gene expression induced by LPS in monocyte-derived macrophages or AMs [10]. The p38 MAPK inhibitor, SD282, is an indole-5-carboxamide selective p38a MAPK inhibitor demonstrating a 14.3-fold greater potency for p38a compared with p38b [8,9].…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, overcoming corticosteroid insensitivity by using p38 MAPK inhibitors can be demonstrated in severe asthmatics. Our data are supported by a recent study that reported that a p38 MAPK inhibitor in combination with dexamethasone caused a greater suppression of gene expression induced by LPS in monocyte-derived macrophages or AMs [10]. The p38 MAPK inhibitor, SD282, is an indole-5-carboxamide selective p38a MAPK inhibitor demonstrating a 14.3-fold greater potency for p38a compared with p38b [8,9].…”
Section: Discussionsupporting
confidence: 77%
“…The incomplete suppression of UP-LPS-induced CXCL8, CXCL1, and CCL5 production from COPD alveolar macrophages in the current study was also observed in our previous work (Armstrong et al, 2009;Kent et al, 2009). We now show that the chemokine concentrations in conditioned media present after corticosteroid treatment cause neutrophil chemotaxis to be maintained at a similar level compared with no corticosteroid treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Viable macrophages were isolated and counted using trypan blue exclusion. We have shown that this method results in .90% cells confirmed as macrophages expressing CD68 (Kent et al, 2009;Southworth et al, 2012).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Alveolar macrophages (AMs) were isolated as previously described (24). Briefly, six smokers (4 men/2 women, mean age 61.7 yr, mean pack-year history 60.3 pack-years) undergoing lung surgery for suspected or confirmed lung cancer, were recruited.…”
Section: Methodsmentioning
confidence: 99%